Natural Clay as a Low-Cost Adsorbent for Crystal Violet Dye Removal and Antimicrobial Activity - Ali Q. Alorabi (MDPI AG, 2021)
This investigation aimed at evaluating the efficiency of micro and nanoclays as a low-cost material for the removal of crystal violet (CV) dye from an aqueous solution. The impacts of various factors (contact time, pH, adsorbent dosage, temperature, initial dye concentration) on the adsorption process have been taken into consideration. Six micro and nanoclay samples were obtained by treating clay materials collected from different locations in the Albaha region, Saudi Arabia. Out of the six tested micro and nanoclays materials, two (NCQ1 and NCQ3) were selected based on the highest adsorption efficiency for complete experimentation. The morphology and structure of the selected micro and nanoclay adsorbents were characterized by various techniques: SEM-EDX, FTIR, XRF, XRD, and ICP-MS. The XRF showed that the main oxides of both nanoclays were SiO2, Al2O3, Fe2O3, K2O, CaO, and MgO, and the rest were impurities. All the parameters affecting the adsorption of CV dye were optimized in a batch system, and the optimized working conditions were an equilibrium time of 120 min, a dose of 30 mg, a temperature of 25 °C, and an initial CV concentration of 400 mg/L. The equilibrium data were tested using nonlinear isotherm and kinetic models, which showed that the Freundlich isotherm and pseudo-second-order kinetics gave the best fit with the experimental data, indicating a physico-chemical interaction occurred between the CV dye and both selected micro and nanoclay surfaces. The maximum adsorption capacities of NCQ1 and NCQ3 adsorbents were 206.73 and 203.66 mg/g, respectively, at 25 °C. The thermodynamic factors revealed that the CV dye adsorption of both micro and nanoclays was spontaneous and showed an exothermic process. Therefore, the examined natural micro and nanoclays adsorbents are promising effective adsorbents for the elimination of CV dye from an aqueous environment.